La protection de la jeunesse en droit comparé - Deleury, Édith; Lindsay, Jocelyn; Rivet, Michèle (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper is an account of the last phase in the work of the Research Project on Children and Young Persons' Law set up in 1974 within the Faculty of Law, Laval University. Its aim is to throw light through a comparative exercise, on the main features and deficiencies of the Youth Protection Act adopted by the Quebec Legislature on December 13, 1977 and progressively put in force over the period ending January 15, 1979. Having in mind the social, legal and cultural context of Quebec, the authors selected for comparative study the legislation on youth protection in England, Belgium, France and the States of New York and California. These had in any case been the legal systems whose influence was most strongly felt in the preparation of the Quebec Act. The paper first attempts to outline the philosophy underlying each of these systems. It then focuses on the provisions for remedial action both in respect of children living in unhealthy or dangerous conditions and of young offenders.